MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN ANAK TUNAGRAHITA RINGAN MELALUI MEDIA FLIP CHART - Chori Yulianda (Jurnal Penelitian Pendidikan Khusus, 2012)
The research was motivated by the problems that researcher found in a field that is on a student's grade II mild Tunagrahita Elementary School 34 Air Pacah Padang. These child have difficulty in identifying symbol number by which he was not familiar with the symbol of number both in terms of counting, reading number symbols, writing and numbers to match the symbol with the number of objects. If the child were ask to answer with the wrong answers. This study used experimental approach in the form of Single Subject Research (single-subject study), with AB design and data analysis techniques using graphical visual analysis. Based on the results of this study shows that student ability to recognize the symbol number Tunagrahita interests can be improved by using the media Flip Chart. Thus the hypothesis (Ha) filed acceptable. This means that media use can improve the skills of Flip Chart familiar symbol for the number of child in grade II mild Tunagrahita Elementary School 34 Air Pacah Padang. Recommended for classroom teacher or subject teacher of Mathematics in order to use the media Tunagrahita Flip Chart for child to know the symbol of light in the teaching of number.